TOPICAL ISSUES OF THE DEVELOPMENT OF PROFESSIONAL AND LEGAL CONSCIOUSNESS AND CULTURE OF EMPLOYEES OF THE INTERNAL AFFAIRS BODIES (Conferencea, 2023)
This article substantiates the relevance of the research topic, on the basis of the analysis of the definitions existing in the scientific literature, the content of the concept of "professional legal awareness" is revealed. The article analyzes the reforms carried out in the internal affairs bodies to raise the system of training, retraining and advanced training, the continuous educational and career process of employees to a new level, as well as the regulatory legal acts adopted in this regard. The system of educational institutions of the internal affairs bodies is also covered.